Food Security and COVID-19: Impacts and Resilience in Singapore - Tortajada, Cecilia; Lim, Nicole Sher Wen (Frontiers in Sustainable Food Systems, 2021)
Across the world, the COVID-19 pandemic has disrupted food supply chains and threatened food security. Singapore is highly dependent on food imports and has an open economy that exposes it to volatile global markets, so it is acutely vulnerable to the effects of the pandemic on other countries, the effectiveness of measures taken by foreign governments to combat the spread of the virus and overall disruptions of international trade links. Proactive and reactive steps have been taken to protect Singapore's food supply chains against the adverse impacts of COVID-19. In this paper, we discuss food security in the city state, the impacts of COVID-19 in the population, the local production, and imports from two main trade partners: Malaysia and China. We conclude by acknowledging the complexity of achieving food security under the very difficult circumstances.